Analysis of The Process of Intensive Guidance in Reading and Writing the Qur'an for Children Aged 8-12 Years At The Pondok Darul Aman Foundation Thailand - Lukman Hakim; Fitrah Sugiarto; Mustahiqur rahman; Salwa Dama Nazila; Muhammad Ridho Rizki Setiawan (Edumaspul: Jurnal Pendidikan, 2025)
This article discusses an intensive Qur'an reading and writing tutoring program designed for children aged 8-12 years at Kalamullah Qur'an and Multilingual School, Al-Rahmah Al-Alamiyah Qur'an Memorization Center, Darul Aman Pondok Foundation in Thailand. The program aims to improve reading, writing, and basic comprehension of the Qur'an at an early age through structured teaching methods and an interactive approach. This research uses a qualitative-descriptive approach, with data collection through observation, interviews, and documentation. The results show that the program significantly helps children improve their skills in reading and writing the Qur'an, with a focus on strengthening a solid foundation of Islamic teaching at an early age. The program also pays attention to aspects of learning motivation and Islamic character building, which contribute to increasing children's interest and love for the Qur'an. The findings make an important contribution to the field of Islamic religious education and can serve as a reference for other educational institutions with a similar vision.